Clinal variation in drought resistance shapes past population declines and future management of a threatened plant. Issue 1 (22nd January 2020) - Krushelnycky, Paul D.; Felts, Jesse M.; Robichaux, Robert H.; Barton, Kasey E.; Litton, Creighton M.; Brown, Matthew D.
Abstract: Predicting vegetation responses to increased future drought is challenging, owing to the complex interaction of multiple factors influencing both plant drought resistance and local climatic conditions, each of which may be subject to spatial and temporal heterogeneity. We conducted a detailed study of potential mechanisms underlying an elevational gradient in mortality that has characterized recent population declines of a threatened alpine plant, the Haleakalā silversword ( Argyroxiphium sandwicense subsp. macrocephalum ). We used a pair of greenhouse experiments staged at high and low elevations to test the influences of plasticity (to contrasting soil water availability and atmospheric conditions) and heredity (different seed source elevations) on the development of functional traits associated with drought resistance and on performance in a terminal drought. We then out‐planted a subset of plants into three common‐garden plots near the bottom, middle, and top of the silversword elevational range, and tracked growth and survival over 3.5 yr. A range of morphological traits (root and leaf mass fractions, specific leaf area, leaf area ratio, and root length per shoot mass) exhibited either heritable variation or plasticity or both. Among physiological traits measured, only water use efficiency exhibited a plastic treatment response. Survival of out‐plants was influenced during the first year by a home site advantage, and by the water treatment imposed in the greenhouses, with high water plants dying more often than low water plants. These effects subsequently dissipated, being replaced over the final 1.5 yr by a strengthening out‐plant site effect: survival was positively associated with site elevation, matching the pattern of mortality observed in the wild population. The balance of information suggests this pattern stems from lower elevation plants being less drought resistant than higher elevation plants, owing principally to plasticity, and thus suffering greater mortality during recent dry seasons. The pattern may be enhanced by stronger deviations from typical climatic conditions at lower elevations. Our findings suggest that future management should focus on climatically suitable habitat rather than advantageous genetic ecotypes. More broadly, they provide evidence that clinal variation can be important to consider when modeling future vegetation responses to climate change.